PENGARUH MOTIVASI KERJA, GAYA KEPEMIMPINAN KEPALA SEKOLAH, DAN SARANA PRASARANA TERHADAP KINERJA GURU SEKOLAH DASAR KECAMATAN PIYUNGAN KABUPATEN BANTUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
This research was a survey research using quantitative correlational research approach. This research was done in 19 elementary schools in Piyungan Subdistrict, Bantul Regency. The population of this research was the elementary school teachers they were 268 people, while the sample 152 peoples. The data were collected using questionnaire and analyzed by multiple regression and continued by partial correlation analysis. The results of this research show that (a) there is positive and significant work motivation, principals’ leadership style and infrastructure on teachers’ performance of elementary school, (b) there is positive and significant influence of work motivation on elementary school teachers’ performance, (c) there is positive and significant principals’ leadership style on teachers’ performance of elementary School and, (d) infrastructure did not give influent on Elementary School teachers’ performance in Piyungan Subdistrict, Bantul Regency.